2012
DOI: 10.3748/wjg.v18.i32.4371
|View full text |Cite
|
Sign up to set email alerts
|

Alginate controls heartburn in patients with erosive and nonerosive reflux disease

Abstract: Our findings demonstrate that Faringel is well-tolerated and effective in reducing heartburn by modifying esophageal acid exposure time, number of acid refluxes and their proximal migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 54 publications
0
61
0
2
Order By: Relevance
“…However, the poor sensitivity and specificity of all currently available diagnostic tests for LPR has been highlighted by several review articles [Altman et al 2011;Katz et al 2013;Vaezi et al 2003]. In a population of patients with laryngoscopic findings of LPR, our group showed that MII-pH confirmed GERD diagnosis in less than 40% of patients [de Bortoli et al 2012], thus highlighting the critical issue of nonspecific symptoms and laryngoscopic findings of LPR [Zerbib and Stoll, 2010]. New promising diagnostic techniques have been developed for extraesophageal reflux syndromes, in particular, an immunologic pepsin assay (Peptest TM ), which has been shown to be a rapid, sensitive, and specific tool [Bardhan et al 2012;Samuels and Johnston, 2010], and a new pH pharyngeal catheter (manufactured by Restech, San Diego, CA, USA) that recent study documented as highly sensitive and minimally invasive device for the detection of liquid or vapors of acid reflux in the posterior oropharynx [Sun et al 2009].…”
Section: Optimal Treatment Of Laryngopharyngeal Reflux Diseasementioning
confidence: 87%
“…However, the poor sensitivity and specificity of all currently available diagnostic tests for LPR has been highlighted by several review articles [Altman et al 2011;Katz et al 2013;Vaezi et al 2003]. In a population of patients with laryngoscopic findings of LPR, our group showed that MII-pH confirmed GERD diagnosis in less than 40% of patients [de Bortoli et al 2012], thus highlighting the critical issue of nonspecific symptoms and laryngoscopic findings of LPR [Zerbib and Stoll, 2010]. New promising diagnostic techniques have been developed for extraesophageal reflux syndromes, in particular, an immunologic pepsin assay (Peptest TM ), which has been shown to be a rapid, sensitive, and specific tool [Bardhan et al 2012;Samuels and Johnston, 2010], and a new pH pharyngeal catheter (manufactured by Restech, San Diego, CA, USA) that recent study documented as highly sensitive and minimally invasive device for the detection of liquid or vapors of acid reflux in the posterior oropharynx [Sun et al 2009].…”
Section: Optimal Treatment Of Laryngopharyngeal Reflux Diseasementioning
confidence: 87%
“…Patients were only allowed to take alginates, on as-needed basis, as rescue therapy for controlling typical GERD symptoms. 16 Patients who completed the MII-pH study received a double dose of PPI (Esomeprazole 40 mg b.d.) for at least 6 weeks (range 6-8) and, thereafter, the Fisman Cough Severity/Frequency Scores were re-assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, some interesting studies, performed by means of MII-pH analysis, evaluated the effectiveness of raft-forming gel formulation in "add-on" treatment for GERD symptoms. These studies have clearly demonstrated the efficacy of raft-forming gel preparation in reducing the total number of refluxes and their proximal migration [90][91][92] .…”
Section: Multichannel Intraluminal Impedance and Phmentioning
confidence: 99%